FRAUD PERBANKAN SYARIAH DAN MORALITAS KEISLAMAN - Edy Junaedi; Irwan Maulana (STAI Asy-Syukriyyah, 2014)
The accounting scandal is the real picture of accounting frouds in the global world, these frouds are mostly dificult to detect through only regular accounting check or audit, this problem has not been solved until now. Enron Corporation, Lehman Brothers Bankruptcy in the global world, Century Bank and Mega Bank scandal are financial problematic situation. To be Exposed of fraud cases in the banking sector are detrimental to customers and the bank.The purpose of this research is to reveal and analyze factors that trigger of the occurraence of fraud commited by bank employees in the banking business in Indonesia and also implementation of anti fraud strategy in the banking institution to prevent the banking crimes commited by bank employees and how islamic rules in frauds banking institution, according to the purpose of the research methods used are normative research as well as the empirical one because this research will utilize secondary data, which will be followed by an empirical study by observation with expert opinion about fraud in banking institution.The research result indicated that factors that trigger the occurence of frauds committed by bank employees in the banking institution in Indonesia generally can be clasified as fraud triangle which are the pressure to perform fraud (pressure), the opportunities that can be exploited (opportunity) as well as the justification for such action (razionalization) and prospect for the application of anti fraud strategy of banking institution to prevent banking crimes commited by employees, according to most of the Indonesian banking expert on their statement less so prospective, while the implementation of circular letter of Bank Indonesia number 13/28/DPNP in Bank Syariah Mandiri, Bank BTN Syariah Bank Muamalat has not shown any significant decline in case of fraud. Generally, bank put more emphasis on whistleblowing strategy of detection pillar. Integrity is best action for making secure bank from crimes commited by employee with value of Islam and it isnot integrity to institution, just for Alloh.